2018
DOI: 10.3390/info9050119
|View full text |Cite
|
Sign up to set email alerts
|

Fast Identification of High Utility Itemsets from Candidates

Abstract: High utility itemsets (HUIs) are sets of items with high utility, like profit, in a database. Efficient mining of high utility itemsets is an important problem in the data mining area. Many mining algorithms adopt a two-phase framework. They first generate a set of candidate itemsets by roughly overestimating the utilities of all itemsets in a database, and subsequently compute the exact utility of each candidate to identify HUIs. Therefore, the major costs in these algorithms come from candidate generation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Most researchers have been focusing on how to eliminate redundant candidates during the process of mining HUIs; however, the time needed to compute the utility value of itemsets is a significant part of the whole running time. To reduce the long runtime of utility computation, Qu et al [26] thus presented the basic identification algorithm (BIA) for mining HUIs. They then proposed a candidate tree with a novel structure and based on this developed a candidate tree-based algorithm called the fast identification algorithm (FIA) to quickly identify HUIs.…”
Section: High-utility Itemset Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers have been focusing on how to eliminate redundant candidates during the process of mining HUIs; however, the time needed to compute the utility value of itemsets is a significant part of the whole running time. To reduce the long runtime of utility computation, Qu et al [26] thus presented the basic identification algorithm (BIA) for mining HUIs. They then proposed a candidate tree with a novel structure and based on this developed a candidate tree-based algorithm called the fast identification algorithm (FIA) to quickly identify HUIs.…”
Section: High-utility Itemset Miningmentioning
confidence: 99%
“…Itemset is used; if R has a utility confidence value (R.uconf ) greater than or equal to min-uconf (line 24), R is added into the results (line [25][26][27]. If R is valid, Q is enqueued in the list of child nodes of L i (lines 32-37).…”
Section: Algorithmmentioning
confidence: 99%
“…Later, Tseng et al [5] proposed an improved version of UP-Growth, called UP-Growth+, which reduces overestimated utilities. To minimize the cost of candidate generation and utility calculation from two-phase HUIM algorithms, Qu et al [25] proposed a novel tree structure for storing candidates and a tree-based algorithm to quickly identify HUIs. Experimental results showed that the proposed candidate tree structure and the algorithm outperforms the performance of two-phase algorithms.…”
Section: Related Work a High-utility Itemset Miningmentioning
confidence: 99%